Analysis of the implementation of village fund management policies in Hutapadang Village, South Tapanuli Regency - Mualim Hasibuan; Elfi Syahri Ramadhona; Nur Hakima Akhriani Nasution; Martua Siregar; Fitri Romatio Lubis (LEGAL BRIEF, 2022)
This study aims to analyze the implementation of village fund allocation management (ADD) policies on development in Huta Padang village, South Tapanuli Regency. This study aimed to determine the differences in village fund management policies before and after the village fund management policy regarding the means of mobilizing access to transportation, public services, and income levels in Hutapadang Village, South Tapanuli Regency. The type of research used is qualitative research. The sampling technique used was the purposive sampling technique. The data collection method was carried out by in-depth interviews. Data analysis was carried out using an interactive analysis model analysis. The study’s results showed that the village fund policy implementation went quite well. Factors that support the success of the communication dimension are program socialization and information about optimally running Village fund management. In other aspects, namely the bureaucratic structure, coordination between implementers is quite intensive; the relationship is collaborative between policy actors or implementers. The inhibiting factor arises from the resource dimension due to the limited budget of village funds for community empowerment in South Tapanuli Regency, so empowerment activities have not been carried out to improve rural communities’ welfare.